Proposed an upgrading of beauty and health spa at No.5, Jalan PP3, Bandar Universiti, 32610 Seri Iskandar Perak for Ratna Mutiara Enterprise / Hasmahani Azizan - Azizan, Hasmahani (Faculty of Architecture, Planning and Surveying, 2012)
This project is about proposed upgrading of beauty and health spa at No.5 Jalan PP3, Bandar Universiti, 32610 Seri Iskandar, Perak Darul Ridzuan.The client is Ratna Mutiara Enterprise. The aim for this project is to create a systematic flow complete with all treatment area to make comfort for customer to get the service. The design should be welcoming environment to the spa and can be identify the general design requirement of the health spa. In Malaysia, almost spa just provide external beauty only like massage, facial, pedicure, manicure and so on, but they are not take care about internal beauty or health. Based on main products, it provides internal and external beauty products. Nowadays, people accept spa as black story like ‘rumah urut’ and give ‘additional’ services. So, that is the right time to make spa as professional work like other profession. Besides that, this spa also has a lot of design problems. There are not welcoming environment like a spa. The space arrangement also not systematic and there have no privacy area at certain treatment like sauna and milk bath. The scheme colour actually should be suitable with concept or products but this spa used many colour like yellow, red and green. The concept of this project is about purification and suitable with services and products that be used by Ratna Mutiara Enterprise. The colour scheme should be more natural colour because there have not provide spa only but there have health consultant that give advice or to promote the products.